Perancangan Sistem Inventaris Barang Berbasis Web di SMKS Gajah Mada Banyuwangi - Sya'diyah, Nur Halimatus; Aslamiyah, Sulaibatul (Jurnal Informatika dan Komputer, 2025)
The process of managing inventory of goods at SMK Gajah Mada Banyuwangi is currently still done manually, namely by recording goods data in notebooks or using spreadsheet applications such as Microsoft Excel. This manual method causes various problems in the process of managing inventory data, such as lack of time efficiency, potential recording errors, difficulty in finding goods information, and the slow process of making inventory reports required by the school. This condition has an impact on the less than optimal supervision of the availability and condition of goods. To solve this problem, the author conducted a study aimed at building a web-based goods inventory system at SMKS Gajah Mada. The system development method used in this study is the waterfall method with stages of analysis, system design, implementation, testing and maintenance. The analysis stage is divided into two stages, namely needs analysis and system design analysis. In the needs analysis stage, the author conducted interviews, observations, documentation and literature studies. While in the system design analysis stage, the UML diagram is used to describe the user flow and create an interface display. For the system design stage, the author designed the structure of the login form, goods form, borrowing form, return form and borrowing hours form and reporting. In the implementation stage, the author carried out the coding process, which aims to adjust the system design and analysis results that have been designed previously. Furthermore, in the testing stage, the author checked whether all features in the system were running properly. In the maintenance stage, the system will be monitored and repaired if errors or deficiencies are found when used. The expected result of this study is an inventory processing system at SMKS Gajah Mada Banyuwangi.